Studying the Effect of Worker Productivity and the Intensity of Research and Development on the Export Behaviors of Small and Medium Export Companies in Khorasan Razavi Province - RAHIMI, FARNAZ (The journal of contemporary issues in business and government, 2021)
In this study, an attempt has been made to study the effect of workers' productivity and the intensity of research and development on the export behaviors of small and medium-sized export companies in Khorasan Razavi province. The present study is a measurement research in the method research and at the purpose of the goal is, the research to usage and development study. The statistical population of this research is the managers of small and medium export companies in Khorasan Razavi province. The sampling method was based on simple random sampling. A questionnaire was used to collect the required information. A questionnaire was used to collect the required information. This research is based on structural equations and for data analysis, partial least squares method and Smart PLS software have been used. The results showed that workers' productivity had a significant effect on export behaviors and the intensity of research and development of small and medium export companies in Khorasan Razavi province also, the effect of research intensity on the development of small and medium export companies in Khorasan Razavi province has been positive.